Pengaruh Lingkungan Kerja, Budaya Organisasi, Pengembangan Karyawan dan Kepuasan Kerja terhadap Retensi Karyawan Generasi Y di PT Pamapersada Nusantara - Husain Nurisman (Jurnal Ekonomi, 2018)
The aim of this study to investigate the impact of Work Enviroment, Organization Culture, Employee Development, Job Satisfaction to Gen Y Employee Retention using Structure Equation. The data is obtained from 225 Gen Y employees from PT Pamapersada Nusantara. The responden ware chosen by Proportionate Stratified Sampling Technique. The data was collected with questionaire and analysis with Structure Equation Modeling (SEM). Result of this study is there is a significant impact of Work Enviroment, Organization Culture, Employee Development to Job Satisfaction and there is no significant impact of Work Enviroment, Organization Culture, Employee Development, to Employee Retention also there is indirect effect of Organizational Culture and Employee Development to Employee Retention through Job Satisfaction.